MEDIATISASI AGAMA (PEMBINGKAIAN MEDIA KOMPAS.COM TERHADAP ISU PEMERKOSAAN OLEH OKNUM PENGASUH PESANTREN) - Furqon, Syihabul; Busro, Busro (al-Balagh : Jurnal Dakwah dan Komunikasi, 2017)
FramingÂ analysis, methodically is used to dissect discourse impulses that leading to stigma crystallization. Media frames an issue by using language tools and plays a subconscious role in the attitude and understanding of society. Although, basically, every media does framing, but the problem that comes next is when this framingÂ becomes an interest to postulate the lame proposition socially and logically. This research efforts to analyze in narrativeÂ about how religion is mediated by Kompas.com, through framingÂ information issue about the Rape by the Board of Pesantren issue in framingÂ analysis of Zhongdang Pan andÂ Gerald M. Kosicki. In conclusion, the Kompas electronic media framingÂ gives rise to a certain tendency toward the negative stigma of pesantren in the publicÂ through a narrowing of news content in the media, especially from the interpretation and reporting analysis that revolves around closed syntactic and syntagmatic interactions.